2015
DOI: 10.1007/s00170-015-7305-x
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and detection of flaws in pre-cured CFRP using laser displacement sensing

Abstract: The novelty of the research is the detection of different types of flaws in the prepreg carbon fibre-reinforced fibres (CFRP) layup compared to in cured products. This paper presents the development of a new method for in situ detection of prepreg CFRP production flaws combining laser displacement sensors and analytical modelling. Experimental results are used to validate the results from the models. The pre-cured flaws are simulated to determine the needed specifications of the measurement system. In static a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Furthermore, these previously mentioned defect types are commonly applied as example defects in the related research (Oromiehie et al 2019;Harik et al 2018;Heinecke and Willberg 2019) Additionally, foils as typical foreign bodies in manufacturing processes are considered. They show quite different reflection properties in comparison with layed up fibre material (Potter 2009;Miesen et al 2015).…”
Section: Manufacturing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these previously mentioned defect types are commonly applied as example defects in the related research (Oromiehie et al 2019;Harik et al 2018;Heinecke and Willberg 2019) Additionally, foils as typical foreign bodies in manufacturing processes are considered. They show quite different reflection properties in comparison with layed up fibre material (Potter 2009;Miesen et al 2015).…”
Section: Manufacturing Processmentioning
confidence: 99%
“…They demonstrated that a LLSS is a suitable system for fabric and preform inspection. Miesen et al (2015) proposed a method for detecting defects with a point laser displacement system. They discussed factors influencing deviations in their research and analysed the accuracy of such systems.…”
Section: Sensor Based Inspection and Data Processingmentioning
confidence: 99%
“…CPT in this application case is about 0.125 mm. For the thickness measure + indicates an increase in thickness and -means a decrease in thickness compared to the deposited fibre material (Miesen et al 2015;Potter 2009). Following, feasible techniques for the recording of these defects are explained.…”
Section: Manufacturing Processmentioning
confidence: 99%
“…They aimed to find and measure wires with a diameter between 0.5 mm and 1 mm, which were incorporated into CFRP laminates. Miesen et al (2015) suggested a method to sense defects with a point measurement laser displacement system. Additionally, they discussed influencing factors for deviations in their research and analysed the accuracy of such a system.…”
Section: Sensors For Data Acquisitionmentioning
confidence: 99%
“…Our previous studies [5] presented experimental comparison of the abovementioned four sensors in measuring tilted surfaces. Applications of this sensor can be found in many publications [6][7][8][9][10][11][12][13]. Simpler and thus lowercost configuration of this sensor is also a crucial advantage in industrial applications.…”
Section: Introductionmentioning
confidence: 99%